Estudo de eficiência em alguns hospitais públicos e privados com a geraç\~ao de rankings - Alexandre Marinho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– Performance Indicators (PI) has been frequently used as tools for hospitals performance evaluation in Brazil. The presente work evaluates four public and two private hospitals using that approach and a frontier methodology referred in the literature as Data Envelopment Analysis (DEA). DEA was able to assess the observed consumption and production levels of the hospitals and their ability to transform resources into services in a efficient way.
Keywords: 330; Krankenhaus; Unternehmenserfolg; Data-Envelopment-Analyse; Brasilien